Literatur Review Potensi Kandungan Antioksidan Buah Tin dalam Pencegahan Penyakit Stroke - Desy Nurdianty; Rachmat Faisal Syamsu; Nadra Maricar (2023)
According to the World Health Organization (WHO), 15 million people suffer from stroke worldwide every year. Of this number, 5 million died and another 5 million were permanently disabled. The prevalence of stroke in Indonesia based on the diagnosis of people who had a stroke increased in 2018, there were 7% of the population who had a stroke in 2013 and became 10.9% in 2018. Figs contain good nutrition and can be used as a source of minerals and vitamin. Fresh or dried figs contain high levels of fiber and polyphenols. Apart from that, the antioxidant content in figs can protect lipoproteins in plasma from oxidation, resulting in an increase in the amount of plasma antioxidants which improves. Objective: This study aims to determine the potential antioxidant content of figs in preventing stroke. Method: This article was prepared using a literature review method by referring to national and international literature that is considered relevant to the keywords used. There were 12 articles obtained through the Google Scholar, Pubmed, Elsevier, NCBI, and Clinical Key databases. Results: The results of the article review carried out can be concluded that the antioxidant content of figs is flavonoids, polyphenols and etonal which have the potential to prevent stroke.